Impact of Upward Oxygen Diffusion From the Oceanic Crust on the Magnetostratigraphy and Iron Biomineralization of East Pacific Ridge-Flank Sediments - Höfken, Adrian Felix; von Dobeneck, Tilo; Kuhn, Thomas; Kasten, Sabine (Frontiers in Earth Science, 2021)
Recent measurements of pore-water oxygen profiles in ridge flank sediments of the East Pacific Rise revealed an upward directed diffusive oxygen flux from the hydrothermally active crust into the overlying sediment. This double-sided oxygenation from above and below results in a dual redox transition from an oxic sedimentary environment near the seabed through suboxic conditions at sediment mid-depth back to oxic conditions in the deeper basal sediment. The potential impact of this redox reversal on the paleo- and rock magnetic record was analyzed for three sediment cores from the Clarion-Clipperton-Zone (low-latitude eastern North Pacific). We found that the upward directed crustal oxygen flux does not impede high quality reversal-based and RPI-refined magnetostratigraphic dating. Despite low and variable sedimentation rates of 0.1-0.8 cm/kyr, robust magnetostratigraphic core chronologies comprising the past 3.4 resp. 5.2 million years could be established. These age-models support previous findings of significant local sedimentation rate variations that are probably related to the bottom current interactions with the topographic roughness of the young ridge flanks. However, we observed some obvious paleomagnetic irregularities localized at the lower oxic/suboxic redox boundaries of the investigated sediments. When analyzing these apparently remagnetized sections in detail, we found no evidence of physical disturbance or chemical alteration. A sharp increase in single-domain magnetite concentration just below the present lower oxic/suboxic redox boundary suggests secondary magnetite biomineralization by microaerophilic magnetotactic bacteria living as a separate community in the lower, upward oxygenated part of the sediment column. We therefore postulate a two-phased post-depositional remanent magnetization of ridge flank sediments, first by a shallow and later by a deep-living community of magnetotactic bacteria. These findings are the first evidence of a second, deep population of probably inversely oriented magnetotactic bacteria residing in the inverse oxygen gradient zone of ridge flank sediments.